2022
DOI: 10.53730/ijhs.v6ns6.10774
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar tuberculoma in an immunocompetent patient

Abstract: Background: Tuberculosis infection of the Central Nervous System is the major cause of death and morbidity in developing countries. The clinical manifestations and radiological findings in tuberculoma are nonspecific. This article reports a rare case of cerebellar tuberculoma with the manifestation related to an intracranial mass and without the typical clinical symptoms of Tuberculosis in an immunocompetent patient. Case Report: A 20-year-old female with seizure, headache, and vertigo. A mass in the posterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…A literature review was done of reported cases of posterior fossa tuberculosis in immunocompetent adults. 29 , 30 , 31 , 32 , 33 , 34 , 35 Interesting findings were noted. We found 9 cases in the literature, 6 patients out of the 9 were females.…”
Section: Discussionmentioning
confidence: 91%
“…A literature review was done of reported cases of posterior fossa tuberculosis in immunocompetent adults. 29 , 30 , 31 , 32 , 33 , 34 , 35 Interesting findings were noted. We found 9 cases in the literature, 6 patients out of the 9 were females.…”
Section: Discussionmentioning
confidence: 91%